Digging deeper: structural background of PEGylated fibrin gels in cell migration and lumenogenesis. Issue 8 (24th January 2020) - Shpichka, A. I.; Konarev, P. V.; Efremov, Yu. M.; Kryukova, A. E.; Aksenova, N. A.; Kotova, S. L.; Frolova, A. A.; Kosheleva, N. V.; Zhigalina, O. M.; Yusupov, V. I.; Khmelenin, D. N.; Koroleva, A.; et al.
Abstract : Fibrin is a well-known tool in tissue engineering, but the structure of its modifications created to improve its properties remains undiscussed despite their importance, e.g. in designing biomaterials that ensure cell migration and lumenogenesis. Abstract : Fibrin is a well-known tool in tissue engineering, but the structure of its modifications created to improve its properties remains undiscussed despite its importance, e.g. in designing biomaterials that ensure cell migration and lumenogenesis. We sought to uncover the structural aspects of PEGylated fibrin hydrogels shown to contribute to angiogenesis. The analysis of the small-angle X-ray scattering (SAXS) data and ab initio modeling revealed that the PEGylation of fibrinogen led to the formation of oligomeric species, which are larger at a higher PEG : fibrinogen molar ratio. The improvement of optical properties was provided by the decrease in aggregates' sizes and also by retaining the bound water. Compared to the native fibrin, the structure of the 5 : 1 PEGylated fibrin gel consisted of homogenously distributed flexible fibrils with a smaller space between them. Moreover, as arginylglycylaspartic acid (RGD) sites may be partly bound to PEG-NHS or masked because of the oligomerization, the number of adhesion sites may be slightly reduced that may provide the better cell migration and formation of continuous capillary-like structures.